Parental Perspectives about Research and Knowledge Translation in Juvenile Idiopathic Arthritis. Issue 3 (29th January 2020) - Wright, Julia; Curran, Janet; Rose‐Davis, Benjamin; Cellucci, Tania; Duffy, Ciarån M.; Tucker, Lori B.; Batthish, Michelle; Huber, Adam M.; Lang, Bianca; Levy, Deborah M.; Rumsey, Dax G.; Watanabe Duffy, Karen N.; et al.
Abstract : Objective: To identify barriers and facilitators to the uptake of information from research by parents of children with juvenile idiopathic arthritis (JIA). Methods: Parents of children with JIA participated in focus group and telephone interviews at four Canadian pediatric rheumatology centers. The semistructured interviews focused on perceptions about JIA research, how new information about JIA was obtained and used, and what information was of most interest. Transcripts were analyzed using a general inductive approach. Results: Twenty‐eight parents participated in the study. Parents were very interested in research that addresses the outcomes of JIA and side effects of medications. Parents communicated an expectation that information from research be communicated to them by their child's pediatric rheumatologist as part of clinical care. Parents felt that it would be helpful to have information available to them in a variety of formats including written, video, and online. The timing of information delivery is an important factor, with parents being most interested and engaged in learning about new information about JIA at diagnosis and disease flares. We found that parents were overall unaware of new findings from JIA research and therefore may not be optimally utilizing this potentially helpful information in the care of their children. Conclusion: This study has led to an understanding of Canadian parents' perceptions about research and existing gaps in the translation of research knowledge. This information will facilitate the development, implementation, and evaluation of future knowledge translation interventions aimed at improving the uptake of research information in the care of children with JIA.